Animal Citizenship, Phenomenology, and Ontology: Some reflections on Donaldsons & Kymlickas Zoopolis (Bangladesh Journal of Bioethics, 2017)
This paper is a dialogue with Sue Donaldsons and Will Kymlickas book Zoopolis: A Political Theory of Animal Rights. My thesis is that, despite the authors reticence, considerations in first philosophy regarding humans and nonhumans are relevant to their goal of building a more comprehensive animal rights philosophy. What is more, I believe that first philosophy actually can be of help for their proposal, specifically in the form of phenomenology and phenomenological ontology. For this purpose, I first summarize the basic outline of Zoopoliss position and indicate some questions that arise from a strictly internal consideration of its theses. And secondly, I introduce some aspects in which phenomenological research would be relevant, along with some particular and provisional analyses carried out from the standpoint of a phenomenologically-based ontology. Especially, there is a theme that stands out: the intersubjective realms between humans and nonhumans.